PEMANFAATAN SUDUT BACA AKTIF BERBASIS GAMEFIKASI UNTUK PENGUATAN LITERASI SISWA SEKOLAH DASAR - Siti Bulandari; Susan Octavia Ramadani Uspan; Risma Junita Astuti; Zikrina Khalifa Nur; St Marwah; Syafruddin Muhdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low reading interest among elementary school students has become one of the factors affecting students’ literacy skills. Therefore, innovative learning strategies are needed to create an engaging and motivating learning environment. This study aimed to describe the implementation of a gamification-based literacy innovation program through reading corners in elementary schools and to analyze its impact on students’ reading interest and literacy skills. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of elementary school students and classroom teachers. The implemented program integrated gamification elements, such as points, levels, and rewards, into reading activities conducted in the classroom reading corner. The findings revealed that the implementation of the gamification-based literacy program was able to increase students’ reading interest, create a more enjoyable learning atmosphere, and encourage students’ active participation in literacy activities. In addition, the program contributed to improving students’ reading comprehension skills and reading habits. Thus, the gamification-based literacy innovation program can serve as an effective alternative learning strategy to enhance the quality of literacy in elementary schools.